Trends in weight, height, BMI and obesity in schoolchildren from Santa Rosa (Argentina), 1990–2005/07 - Orden, Alicia Bibiana (2013)
Aim: To assess secular changes in physical growth and the current prevalence and trend of overweight/obesity in Argentinian schoolchildren. Subjects and methods: One thousand and forty-nine schoolchildren aged 6 and 12 years attending schools in 1990 were compared with an age-matched sample of 935 boys and girls collected between 2005–2007. Changes in weight, height and BMI by age between the surveys were analysed using one-way analysis of variance. Overweight and obesity were defined according to IOTF criteria and compared by Chi-squared test. Odds ratios (OR) and intervals of confidence (95% CI) were also calculated. Results: Six and 12 year-old boys and girls were significantly heavier (1.2–3.2 kg) and had higher BMIs (0.7–1.0 kg/m2 ) in 2005–2007 than in 1990. Significant differences in height were seen in 6 year old boys (1.5 cm) and 12 year old girls (1.3 cm). Overweight and obesity increased by 4.4% (OR ¼ 1.4, 1.1–1.8) and 5.9% (OR ¼ 4.3, 2.8–6.5), respectively; obesity being higher in younger children. Conclusion: The disharmonic secular change in weight and height has led to high overweight/ obesity. The obesity increase is consistent with global and regional trends, indicating a shift in BMI distribution, especially at the higher centiles.